Involvement of astrocyte senescence in Alzheimer's disease. (October 2022) - Tuzer, Ferit; Torres, Claudio
Highlights: Senescent astrocytes lose neuron-supportive function. Senescent astrocytes and other CNS cell types increase in Alzheimer's disease (AD). Targeting senescence in these cell types has reversed pathology in AD mouse models. Many drugs that modulate or clear senescence have been tested in clinical trials. Senescence clearing compounds (senolytics) are now being tested in AD patients.